(untitled) (Mustansiria Dental Journal, 2019)
Background: Age estimation plays a great role in forensic investigations, orthodontic, surgical treatment planning and tooth transplantation. The teeth are considered a reliable indicator of age and provide a number of parameters for age prediction. The purpose of this study was to estimate the chronological age based on the stages of mandibular third-molar eruption following the four stages given by Olze et al. Materials and methods: The sample consist of 150 Iraqi subjects have been chosen with known chronologic age (range: 6–26 years) and gender (70 males and 80 female), digital panoramic radiograph had been taken for each examined subject . Olze et al. stages has been used to assess third molar eruption. Results: Alveolar and occlusal eruption at 25% of males younger than females . T-test between gender for minimum age was statistically significant difference only in stage (B) with p-value (0.042).The deviation around normal value mean in complete occlusal eruption was more in female compared with male. Conclusions: Radiographic evaluation of eruption stages of the third molars using dental panoramic radiographies can be an efficient tool for chronological age estimation in both forensic science and legal medicine. Complete occlusal eruption can be used to predict age equal or superior to 16 years.